The Relationship Between Leg Length and Leg Strength and Ability to Kick the Ball in Football Games - Bismar, Ahmad Rum; Amahoru, Nurul Musfira (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to determine the relationship between leg length and leg strength with the ability to kick the ball in a football game. This research is a type of correlational descriptive research. The population of this study is all students of SMP Negeri 24 Makassar with a research sample of 100 male students selected by proportional random sampling. The data analysis techniques used are simple and multiple correlation analysis techniques. Based on the results of data analysis, this study concludes that: There is a significant relationship between leg length and the ability to kick the ball in a football game, (ro = 0.508 > rt = 0.220); There was a significant relationship between leg strength and the ability to kick the ball in a football game, (ro=0.693 > rt=0.195); There was a significant relationship between leg length and leg strength with the ability to kick the ball in a football game (Ro = 0.708 > Rt = 0.195).